Dental resin monomer enables unique NbO2/carbon lithium‐ion battery negative electrode with exceptional performance - Ji, Qing; Gao, Xiangwen; Zhang, Qiuju; Jin, Liyu; Wang, Da; Xia, Yonggao; Yin, Shanshan; Xia, Senlin; Hohn, Nuri; Zuo, Xiuxia; Wang, Xiaoyan; Xie, Shuang; et al. (Wiley-VCH Verlag, 2019)
Niobium dioxide (NbO2) features a high theoretical capacity and an outstanding electron conductivity, which makes it a promising alternative to the commercial graphite negative electrode. However, studies on NbO2 based lithium-ion battery negative electrodes have been rarely reported. In the present work, NbO2 nanoparticles homogeneously embedded in a carbon matrix are synthesized through calcination using a dental resin monomer (bisphenol A glycidyl dimethacrylate, Bis-GMA) as the solvent and a carbon source and niobium ethoxide (NbETO) as the precursor. It is revealed that a low Bis-GMA/NbETO mass ratio (from 1:1 to 1:2) enables the conversion of Nb (V) to Nb (IV) due to increased porosity induced by an alcoholysis reaction between the NbETO and Bis-GMA. The as-prepared NbO2/carbon nanohybrid delivers a reversible capacity of 225 mAh g−1 after 500 cycles at a 1 C rate with a Coulombic efficiency of more than 99.4% in the cycles. Various experimental and theoretical approaches including solid state nuclear magnetic resonance, ex situ X-ray diffraction, differential electrochemical mass spectrometry, and density functional theory are utilized to understand the fundamental lithiation/delithiation mechanisms of the NbO2/carbon nanohybrid. The results suggest that the NbO2/carbon nanohybrid bearing high capacity, long cycle life, and low gas evolution is promising for lithium storage applications.